Malaria and under-nutrition: a community based study among under-five children at risk of malaria, south-west Ethiopia. - Amare Deribew (Public Library of Science (PLoS), 2010)
Background The interaction between malaria and under-nutrition is not well elucidated in Ethiopia. The objective of this study was to assess the magnitude of under-nutrition and its correlation with malaria among under-five children in south-west Ethiopia. Methods This cross-sectional study was undertaken during March-February, 2009 as part of the baseline assessment of a cluster randomized trial around Gilgel Gibe Hydroelectric dam, south-west Ethiopia. A total of 2410 under-five children were included for anthropometric measurement and blood investigation for the diagnosis of malaria and anemia. The nutritional status of children was determined using the International Reference Population defined by the U.S National Center for Health Statistics (NCHS). Blood film was used to identify malaria parasite and haemoglobin concentration was determined by Hemo Cue analyzer (HemoCue Hb 301, Sweden). Results Significant proportion (40.4%) of under-five children were stunted (height-for-age<-2SD). The prevalence of under-weight was 34.2%. One third and one tenth of the children had anemia and malaria parasite respectively. Older children were more likely to have under-nutrition. There was no association between malaria and under-nutrition. Children who had malaria parasite were 1.5 times more likely to become anaemic compare to children who had no malaria parasite, [OR = 1.5, (95% CI: 1.1-2.0)]. Conclusion In this study, there is no association between malaria and under-nutrition. Children who have malaria are more likely to be anaemic. Malaria prevention and control program should consider nutrition interventions particularly anemia.